Efficacy and Mechanism of Electroacupuncture Treatment of Rabbits With Different Degrees of Knee Osteoarthritis: A Study Based on Synovial Innate Immune Response - Ruan, Anmin; Wang, Qingfu; Ma, Yufeng; Zhang, Dong; Yang, Lili; Wang, Zhongpeng; Xie, Qi; Yin, Yueshan (Frontiers in Physiology, 2021)
Knee osteoarthritis is a chronic degenerative bone and joint disease.Its pathological manifestations are mainly synovial inflammation and cartilage degeneration. The study aims to explore the efficacy of EA in different degrees of KOA rabbits and the mechanism of EA on KOA based on the innate immune response. The modified Hluth method was to establish rabbit models of mild and moderate KAO, the mild and moderate model groups were given electro-acupuncture treatment respectively. The Lequesne-MG index was to assess the behavioral changes of the rabbits before and after treatment. HE staining to observe the morphological changes of synovium and cartilage in each group, enzyme-linked ELISA to detect the content of inflammatory factors and mechanism metalloproteinases in rabbits of each group, western blot, and qPCR Detect the protein and mRNA expression of TRLs-mediated innate immune response-related elements in synovial tissue. We found that the Lequesne-MG index score of rabbits gradually increased with the extension of the modeling time, and the Lequesne-MG index score of rabbits was significantly reduced after EA treatment, indicating that EA has a better effect in improving pain and alleviating dysfunction. The morphological results showed that the inflammation and damage of the synovial membrane and cartilage tissue gradually increased with the modeling time extension, and the inflammation of the synovial membrane significantly improved after the EA treatment. The cartilage damage repaired; The ELISA results showed that the serum related inflammatory factors and mechanism of metalloproteinases gradually increased with the modeling time and decreased after EA treatment. Western blot and qPCR results showed that the protein and mRNA expression of related innate immune response elements in the synovial membrane increased gradually with the extension of modeling time, all decreased significantly after EA treatment. Simultaneously, the expression of some components in the electro-acupuncture group 1 was significantly lower than that in the electro-acupuncture group 2. These results confirm that synovial inflammation gradually aggravated with time in the early to mid-stage. Electro-acupuncture may have a therapeutic effect on KOA by inhibiting TLRs-mediated synovial innate immune response, and electro-acupuncture should be used in the early stage of KOA. Treatment can achieve better results.